A study of anaemia and its correlates among adolescent girls in schools of Haldwani, India - Goyal, Neha; Rawat, C. M. S. (International Journal of Research in Medical Sciences, 2018)
Background: Anaemia, a manifestation of under nutrition and poor dietary intake of iron is a public health problem, not only among pregnant women, infants and young children but also among adolescents. Anaemia among adolescent girls can result in impaired physical growth, poor cognition, reduced physical fitness and work performance and lower concentration on daily tasks. Methods: A cross-sectional descriptive study was carried out in schools of Haldwani, Uttarakhand, India with the objective studying various socio-demographic characteristics in relation to anaemia among adolescent girls. Multistage random sampling was used to select adolescent girls of 10 to 19 years of age who were interviewed and examined. Statistical analysis was done using Chi-square test and Odds ratios calculated with SPSS v21. Results: Around 371 girls in present study had varying severity of anaemia and majority had mild to moderate anaemia. Place of residence, type of school, birth order, type of family and mother occupation were significantly associated with presence of anaemia. Girls taking mixed diet were 1.23 times more likely to be non-anaemic as compared to girls taking vegetarian diet. Study showed adolescent girls consuming IFA tablets were less likely anaemic compared to those not consuming (OR=0.09, p<0.001). Conclusions: Among school going adolescent girls nearly half are still suffering from anaemia in India, despite the efforts of government and it is still a challenging public health problem.